M, Manajemen Pembiayaan Sekolah Dasar Yang Efektif: Manajemen Pembiayaan - Suriadi, Ilham; Hamdi Abdul Karim; Nasrin Hasibuan (Global Action and Education for Society, 2026)
The phenomenon of low effectiveness of education funding management in various elementary schools remains a crucial issue in Indonesian education, particularly in terms of accountability, transparency, and integration between budget planning and implementation. This condition results in less than optimal utilization of funds to support improvements in the quality of education services and student learning outcomes. This study aims to examine in-depth aspects of effective elementary school funding management, starting from the sources and types of funding, budget planning strategies, and its impact on education quality. The method used is library research by reviewing various literature, government regulations, and the results of relevant previous research. The results show that participatory, transparent, and performance-based funding management has been proven to increase the efficiency of fund use, encourage the creation of higher-quality education programs, and strengthen public accountability for elementary school financial management. These findings emphasize the importance of strengthening the managerial capacity of school principals and involving all stakeholders in the education budget planning and evaluation process.